Avaliação da performance de remate em atletas de Goalball - Raquel Almeida Santos (2018)
Visual Impairment (VI) can be defined as low vision or blindness condition, through poor eye focus or effective vision loss, that compromises the personal functionality, once it is the sense that allows to obtain about 75% of the sensorial information of the surrounding environment. Facing the existence of VI, the person presents limitations in several areas, including in the motor area. In this context, participation in adapted physical activity (AFA) can bring numerous benefits, stimulating autonomy and motor development, and leading the person to engage in a competitive sports practice. Goalball is a Paralympic sport created to be practiced by people with VI, being currently investigated in different perspectives. The success of the game implies the knowledge of technical gestures of defense and throwing, being the last one determinant in the number of goals on a Goalball team. In this way, the study objective was to verify the effect of the application of a specific training plan for the development of the front throw, through biomechanical movement analysis. It was also intended to evaluate, biomechanically, the final phase of the rotational throw and its difference relative to the front throw. The sample was made up of 17 Goalball athletes, divided into control group (GC) and experimental group (GE), submitted to two stages of throws collection in the Porto Biomechanics Laboratory (LABIOMEP) and a 3-game recording of each group in the National Championship of Goalball. The training plan was applied to GE among the collections and lasted for 3 months. The results revealed did not present any differences between groups on the front throw, being, however, more used and more effective in GE over the period of evaluated games, evidencing the improvement of the technique with respect to the velocity and accuracy. The rotational throw has not improved between collections for both groups being more used and more effective in GC. The specific training plan applied has, positively, influenced the front throw velocity and accuracy of GE athletes.